2008
DOI: 10.1074/jbc.m709776200
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Growth and Endoplasmic Reticulum Stress Signaling by Regulator of Calcineurin 1 (RCAN1), a Novel ATF6-inducible Gene

Abstract: Exposing cells to conditions that modulate growth can impair endoplasmic reticulum (ER) protein folding, leading to ER stress and activation of the transcription factor, ATF6. ATF6 binds to ER stress response elements in target genes, inducing expression of proteins that enhance the ER protein folding capacity, which helps overcome the stress and foster survival. To examine the mechanism of ATF6-mediated survival in vivo, we developed a transgenic mouse model that expresses a novel conditionally activated form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 46 publications
(33 reference statements)
4
104
0
Order By: Relevance
“…The resulting N-terminal fragment of ATF6 translocates to the nucleus, where it binds to several types of regulatory sequences in target genes, such as ER stress elements (ERSEs), and activates ER stress response gene transcription (7, 10, 14, 26 -37). A microarray study in the mouse heart showed that upon activation, ATF6 induced nearly 400 genes (38), supporting the hypothesis that ATF6 is a central regulator of numerous ER stress response genes, many of which may serve protective roles. The current study was undertaken to examine roles for ATF6 in ischemia-mediated ER stress gene induction of a prototypical ER stress response gene, GRP78, in a cultured cardiac myocyte model system of simulated ischemia/reperfusion.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…The resulting N-terminal fragment of ATF6 translocates to the nucleus, where it binds to several types of regulatory sequences in target genes, such as ER stress elements (ERSEs), and activates ER stress response gene transcription (7, 10, 14, 26 -37). A microarray study in the mouse heart showed that upon activation, ATF6 induced nearly 400 genes (38), supporting the hypothesis that ATF6 is a central regulator of numerous ER stress response genes, many of which may serve protective roles. The current study was undertaken to examine roles for ATF6 in ischemia-mediated ER stress gene induction of a prototypical ER stress response gene, GRP78, in a cultured cardiac myocyte model system of simulated ischemia/reperfusion.…”
mentioning
confidence: 86%
“…Each well was incubated for 5 h with 10 pmol of each Stealth siRNA using TransMessenger TM transfection reagent (Qiagen, Valencia, CA), as described previously (38). The cells were then washed off the plates and replated at a density of 0.7 ϫ 10 6 cells/well on fibronectincoated 6-well plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that the expression of PYCR1 mRNA was enhanced in transgenic mice with an activated form of ATF6 (Belmont et al 2008). In fact, we found an ATF6 inhibitor, AEBSF, reduced the expression of PYCR1 under ER stress condition.…”
Section: Discussionmentioning
confidence: 50%
“…Upregulation of Manf by ER stress conditions has been shown by microarray analyses (Lee et al, 2003;Mizobuchi et al, 2007;Belmont et al, 2008), suggesting that Manf has a role in the quality control of proteins during ER stress (Lee et al, 2003). Manf was also upregulated in cell lines by different UPR inducers (Apostolou et al, 2008).…”
Section: Protection Against Er Stressmentioning
confidence: 90%